2020
DOI: 10.1021/acs.jpcc.0c08262
|View full text |Cite
|
Sign up to set email alerts
|

Surface Orientation and Pressure Dependence of CO2 Activation on Cu Surfaces

Abstract: A fundamental understanding of interactions between catalysts and gas molecules is essential for the development of efficient heterogeneous catalysts. In this study, ambient pressure X-ray photoelectron spectroscopy (APXPS) and density functional theory (DFT) simulation were employed to investigate the activation of CO2 on Cu surfaces, which acts as a key step in the catalytic reduction of CO2. APXPS results show that CO2 is adsorbed as CO2 δ− on the Cu(111) surface under a pressure of 0.01 mbar at 300 K. Adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
6
21
0
Order By: Relevance
“…On both surfaces, atomic oxygen was generated that catalyzed the self-deactivation of CO 2 adsorption. The DFT results, which collaborated the experimental findings, further indicated that the Cu (110) surface was more active than the Cu (111) surface in breaking C-O bonds [95]. Comparing the adsorption of CO 2 on Cu ( 111), (100), and (110) surfaces, it was found that CO 2 molecules aligned parallel to Cu ( 111) and ( 100), whereas a vertical configuration was more stable for the adsorbed CO 2 on Cu (110) with one of two oxygen atoms towards the surface.…”
Section: Co 2 Activation On Representative Pure Metalssupporting
confidence: 74%
See 1 more Smart Citation
“…On both surfaces, atomic oxygen was generated that catalyzed the self-deactivation of CO 2 adsorption. The DFT results, which collaborated the experimental findings, further indicated that the Cu (110) surface was more active than the Cu (111) surface in breaking C-O bonds [95]. Comparing the adsorption of CO 2 on Cu ( 111), (100), and (110) surfaces, it was found that CO 2 molecules aligned parallel to Cu ( 111) and ( 100), whereas a vertical configuration was more stable for the adsorbed CO 2 on Cu (110) with one of two oxygen atoms towards the surface.…”
Section: Co 2 Activation On Representative Pure Metalssupporting
confidence: 74%
“…The presence of preadsorbed oxygen was responsible for forming carbonates of different structures [87,93]. On most metal surfaces, CO 2 activation is highly surface orientated, pressure-and particle size-dependent [89,[94][95][96]. Yu et al [96] demonstrated through spin-polarized DFT calculations that adsorption and dissociation of CO 2 was dependent on the Co particle size.…”
Section: Co 2 Activation On Representative Pure Metalsmentioning
confidence: 99%
“…However, theoretical calculations proved that formate is a reactive intermediate for CO 2 conversion to methanol, rather than a spectator, even though it accumulates on the Cu/ZrO 2 surface . Furthermore, DRIFTS, IRRAS, and NAP-XPS studies and theoretical calculations also showed that the activation barrier for the rate-limiting step in the carbonate, formate, and carbonyl pathways is dependent on the catalysts, and the Cu/CeO 2– x interface can lower the activation barrier for the formate pathway. ,,, Thus, in our NAP-XPS study, the RWGS route on the Cu/CeO 2– x surface via CO 2 dissociation in the form of carbonate, the conversion of carbonate to formate, and the decomposition of formate to CO becomes feasible.…”
Section: Resultsmentioning
confidence: 57%
“…Here, shear causes one of the carboxylate oxygens to detach from the surface to initially form an η 1 -acetate species that continues to tilt as the reaction proceeds. This induces the formation of a bent CO 2 δ− species that has been detected on copper at high CO 2 pressures [45,46], which reacts to form CO and adsorbed oxygen.…”
Section: Resultsmentioning
confidence: 97%
“…This suggests an alternative possibility that large stresses parallel to the plane of the adsorbed acetate induces the formation of monodentate acetate species, which then decomposes to form CO and adsorbed oxygen (Fig. 7) via a bent CO 2 δ− intermediate [45,46]. The reaction also deposits methyl species onto the copper surface so that one of the main differences between the thermal and mechanochemical processes is the temperature at which the resulting methyl species are deposited on the surface, where they are formed thermally at ~ 590 K, but tribochemically at ~ 300 K. This will likely influence the subsequent reactions of the products.…”
Section: Discussionmentioning
confidence: 99%